Contemporary figurations in chilean audiovisual fiction: proposals for a historiography of the future - Urrutia Neno, Carolina; Sánchez Sepúlveda, Juan Pablo (Revista de Historia Social y de las Mentalidades, 2023)
This paper considers audiovisual fiction in Chilean cinema and television as a historical document from which we can observe and interpret the present. In this sense, four audiovisual fictions (two films and two television series) inspired by current events, in which reality operates as raw material, will be reviewed. The fictions will be Mala junta (2016), Los perros (2017), El reemplazante (2012) and Bala loca (2016). Its analysis will consider not only the themes, but also the ways in which they are put on screen. Finally, these fictions admit and figure the different problems that account for the malaise through which diverse social groups decided to revolt in 2019.
Keywords: Audiovisual Fiction; Figuration; Social Revolt; Historiography